Uji Validitas dan Reliabilitas Alat Ukur SG Posture Evaluation - Sugiono Sugiono; Noerdjanah Noerdjanah; Afrianti Wahyu (Jurnal Keterapian Fisik, 2020)
Background: The SG Posture Evaluation measuring tool is designed and made to measure changes in posture in adults and children. the level of validity and reliability of the SG Posture Evaluation measuring instrument is needed. The purpose of this study is to determine the level of validity and reliability of the SG Posture Evaluation measuring instrument. The benefits of this study as a scientific reference related to the validity and reliability of the SG Posture Evaluation can be used in the community. Methods: The research method used through quantitative research. The sampling technique is purposive sampling, the number of samples is 84, there are 2 categories and there are 10 claims /items, ranking 5 parallel to the spine and 5 items from the side of the neck (neck, shoulders, thorax, lumbar and pelvis), data discussed with Pearson and apronha cronbach. Results: Valid results, Rating from back: Item number 2 (Shoulder value 323), item number 5 (Pelvic 260) and side-side values obtained: Item number 1 (Neck 747), Item number 2 (Shoulder value 276), Item number 3 (Thoraks value 301), Item number 4 (Lumbar value 489) Item number 5 (Pelvic 334). While invalid results, Value from back: Item number 1 (Neck value 170), Item number 3 (Thorax value 128), Item number (4) (Lumbar value 0); goods. The level of reliability with an alpha cronback value of 612 values greater than 0.6. Conclusion: There is validity and reliability of the SG Posture Evaluation measuring instrument.